Isolation of 2 simazine-degrading bacteria and development of a microbial agent for bioremediation of simazine pollution - ZHU,JIANGWEI (2021)
Abstract Simazine was one of the most commonly used herbicides and was widely used to control broadleaf weeds in agriculture and forestry. Its widespread use had caused wide public concern for its high ecological toxicity. In order to remove simazine residues, 2 strains capable of effectively degrading simazine were isolated from the soil and named SIMA-N5 and SIMA-N9. SIMA-N5 was identified as Bacillus licheniformis by 16SrRNA sequence analysis, and SIMA-N9 was Bacillus altitudinis. According to the degradation ratio of simazine in a certain period of time, the degradation ability of different strains was evaluated. The degradation efficiency of simazine (5 mg/L) by SIMA-N9 could reach about 98% in 5d, and the strain SIMA-N5 could reach 94% under the same conditions. In addition, the addition of Pennisetum rhizosphere soil during the process of degrading simazine by strain SIMA-N9 could effectively improve the degradation efficiency. The strain SIMA-N9 has been developed as a microbial agent for the bioremediation of simazine contamination in soil. The new microbial agent developed by using SIMA-N9 has achieved satisfactory application effects. Based on the research results already obtained in this study, it was considered that strain SIMA-N9 and its live bacterial agent could play an important role in bioremediation of simazine pollution. This study could not only provide a set of solutions to the simazine pollution, but also provide a reference for the treatment of other pesticide pollution.